Expression of Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 in Endometriosis Menstrual Blood - Tita Husnitawati Madjid; Dennis Fachmi Ardiansyah; Wiryawan Permadi; Bethy Hernowo (Diagnostics, 2020)
Endometriosis is a gynecological disease characterized by the presence of endometrial-like tissue outside the uterine cavity. Remodeling of the extracellular matrix (ECM) is a prerequisite for tissue implantation. The presence of matrix metalloproteinase (MMP) and its inhibitor, tissue inhibitor of metalloproteinase-1 (TIMP-1), in shed endometrium cells has a significant role in ECM degradation. A case–control study was performed to find other diagnostic markers using menstrual blood. We examined a sample of 68 women who visited the gynecology clinic in Dr Hasan Sadikin General Hospital, 40% of whom were confirmed to have endometriosis, and the rest tested negative by histopathological examination. All endometriotic cases presented MMP-9 and TIMP-1 expression with different cell distribution. MMP-9 expression in endometriosis patients was increased compared to the controls (p = 0.002). Expression of MMP-9 in >80% of endometrial cells was associated with a higher risk for endometriosis (OR 4.44 95% CI 1.31 to 15.56) compared to MMP-9 expression in 50%–80% of cells. TIMP-1 cell expression in women with endometriosis was lower than in the control group (p = 0.030). Subjects with TIMP-1 expression in 20%–50% of endometrial cells had a higher risk for endometriosis (OR 4.5, 95%CI 1.21–17.42) compared those with TIMP-1 expression in 50%–80% of cells. These expressions levels can be useful to predict endometriosis.